Efek Antiinflamasi Fraksi Heksan dan Fraksi Etil Asetat Daun Alpokat (Persea Americana Mill.) pada Tikus (Rattus Norvegicus) Putih Jantan - Yuslinda, Elka; Hasti, Sylfia; Wati, Erda (Jurnal Sains dan Teknologi Farmasi, 2011)
Avocado (Persea Americana, Mill) has been used traditionally to cure disease but the effect has not proven scientificaly. This study reports the determination of anti inflammation effect of ethyl acetate fraction and hexane fraction of avocado leaves at various dose : 100, 200 and 400 mg/KgBW respectively. Inflammation was induced by using Paw edema method with induction of 1% carrageen 0,5 ml. Phenylbutazone at dose 9 mg/KgBW was used as positive control, while 1% sodium CMC given 1 hr before induction was used as negative control. The edema volume was determined at one hour interval for 5 hours, and percentage of inhibition was then calculated. Result indicated that the ethyl acetate and the hexane fractions of avocado leaves at doses 100, 200, and 400 mg/KgBW showed significant anti-inflammation effect (p<0.05). The best effect was given by the ethyl acetate fraction at dose 400 mg/KgBW.